Benign Beale Gland Hyperplasia Mimicking Malignant Biliary Obstruction - Durairaj Segamalai (Journal of Clinical and Diagnostic Research, 2017)
Extrahepatic bile duct obstruction can be caused by various pathologies, most of them being malignant. Painless, progressive jaundice is the usual mode of presentation. We report a case of distal Common Bile Duct (CBD) obstruction due to a Benign Intramural Beale gland hyperplasia mimicking a periampullary carcinoma. Peribiliary glands (Beale Glands) are a group of seromucinous glands, normally seen within the fibromuscular wall and periductal connective tissue in the extrahepatic and large intrahepatic ducts and also in the neck of the Gall bladder. These glands drain into the bile duct lumen through small channels referred to as sacculi of Beale. Intramural Beale ducts are lobular aggregates of mucous glands that lie within the wall of the bile duct. Beale Gland hyperplasia is uncommon, and is rarely large enough to be visible macroscopically or with imaging as an incidental finding. There are no case reports of this rare entity. It is distinguished from well differentiated bile duct adenocarcinoma by the preservation of the lobular architecture, lack of cytological atypia and lack of perineural invasion. This case is reported for its rarity.